Perilaku Pasien Dalam Penggunaan Obat Antihipertensi Menggunakan HealthBelief Model Di Puskesmas PuhjarakKabupaten KediriPerilaku Pasien Dalam Penggunaan Obat Antihipertensi Menggunakan HealthBelief Model Di Puskesmas PuhjarakKabupaten Kediri - Krisogonus Ephrino Seran (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2025)
Compliance of hypertension sufferers in using antihypertensive drugs can control blood pressure and reduce the risk of long-term organ damage. Health Belief Model is one of the most widely used conceptual models and frameworks in behavioral research and health promotion. This model can reduce the risk of severity as a result of complications from a disease through behavioral changes which are one of the indicators of successful treatment implementation. The purpose of this study was to determine whether there was an influence of patient behavior on the use of antihypertensive drugs at the Puhjarak Health Center, Kediri Regency. The research method is analytical observational with a cross-sectional approach, the number of samples used was 93 respondents, data collection was carried out using a questionnaire , data analysis using multiple linear regression tests. The results have been found, namely with a p value of 0.000 <0.05, which means that there is an influence between the independent variable (perceived susceptibility, perceived severity, perceived benefit, perceived barrier, self-efficacy and cues to action) on the dependent variable (behavior of hypertensive patients in using antihypertensive drugs) and the R Square value (determination coefficient) is 0.526,